2021
DOI: 10.1001/jamanetworkopen.2021.21934
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Mental and Physical Health Among Norwegian Adolescents Before and During the COVID-19 Pandemic

Abstract: Key Points Question Are there differences in self-reported depression symptoms, friendships, physical health, and organized sports participation among adolescents in Norway before vs during the COVID-19 pandemic and across levels of experienced pandemic-related anxiety? Findings This cohort study including 2536 adolescents found that Norwegian adolescents starting high school during the COVID-19-year had lower odds of sports participation than their peers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 54 publications
(168 reference statements)
3
46
0
Order By: Relevance
“…To the extent that our findings reflect a worsening of underlying mental health, this in line with an Icelandic study indicating that self-reported depression increased during the pandemic (24). In contrast, Norwegian survey-based studies indicate no increase up to fall 2020 (25).…”
Section: Discussionsupporting
confidence: 88%
“…To the extent that our findings reflect a worsening of underlying mental health, this in line with an Icelandic study indicating that self-reported depression increased during the pandemic (24). In contrast, Norwegian survey-based studies indicate no increase up to fall 2020 (25).…”
Section: Discussionsupporting
confidence: 88%
“…To the extent that our findings reflect a worsening of underlying mental health, this in line with an Icelandic study indicating that self-reported depression increased during the pandemic [ 24 ]. In contrast, Norwegian survey-based studies indicate no increase up to fall 2020 [ 25 ]. However, the conflicting findings may reflect the timing of data collection since our study has a considerably longer follow-up (until the end of 2021), and the largest effects are found toward the end of the period.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies of short-term consequences (up to summer 2020) show no substantial changes in mental health [ 21 , 23 ]. Two studies follow children to fall 2020, an Icelandic study report deterioration in children’s mental health while a Norwegian study suggests no substantial changes [ 24 , 25 ]. Beyond differences in the observation period, the mixed findings may reflect differences in questionnaire scales, age profiles, sample selections, and settings.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that violence against children and adolescents has increased during the pandemic, yet some give mixed results 8 9 14 15. Our study focused on adolescents‘ diverse experiences of lockdown, including violence.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, their lives were affected in many ways that exposed and aggravated inequalities, not only within countries but also across and between continents 5–7. As a consequence of the pandemic, adolescents are reported to suffer from increased violence8–10 and mental health problems11–13; however, there are variations 14 15. In line with the UN Convention on the Rights of the Child (UNCRC), it is vital to listen to children and adolescents and involve them in decision making on issues of concern to them during the pandemic 16–18…”
Section: Introductionmentioning
confidence: 99%